Hazards inherent to control systems: Case studies and lessons learned. Issue 3 (2nd December 2016) - Cox, Brenton L.; Garner, Stephen W.; Carpenter, Andrew R.; Fecke, Mark T.
Abstract : Control systems are an integral part of almost all chemical processes, regardless of size or complexity. As the demands for performance and safety increase, control systems will only proliferate. With automation comes the ability to develop more complex and interrelated processes, and to respond more rapidly to disturbances. However, increased reliance on control systems, both discrete and continuous, requires increased diligence with respect to their development and testing, as well as the implementation of independent layers of protection. A control system that provides optimal product for typical feed conditions may behave poorly during abnormal conditions, such as idling or turnarounds. Similarly, independent control systems charged with safety instrumented functions may not be called upon to act until they become necessary to prevent or mitigate an emergency situation. To recognize and mitigate hazards associated with control systems, process design and process hazard assessment teams may need to consider these and other potential issues. Presented here is a brief overview of the hazards associated with control systems. Finally, case studies are used to highlight the need for considering the potential hazards associated with control systems, from the design stage, through startup, operation, and turnarounds. © 2016 American Institute of Chemical Engineers Process Saf Prog 36: 273–279, 2017